1997
DOI: 10.1046/j.1472-765x.1997.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Lactobacillus rhamnosus GG from human colonic biopsies

Abstract: The colonization of Lactobacillus rhamnosus GG (ATCC 53103, henceforth L.GG) in five human colonoscopy patients was studied. The test subjects consumed whey drink fermented with the bacterium for 12 d before the colonoscopy. The presence of L.GG was subsequently checked both in the faecal samples and in the colonic biopsies obtained from various locations in the large intestine. In all patients L.GG was the dominant faecal lactic acid bacterium as a result of the administration. In four patients L.GG could als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(71 citation statements)
references
References 0 publications
1
70
0
Order By: Relevance
“…Crociani et al (1995) reported bifidobacterial adhesion to Caco-2 cells to be inconsistent with human colonization by the same strains. Furthermore, probiotic Lactobacillus GG expressing high adhesion to ileostomy glycoproteins in the current study has been shown to adhere to the Caco-2 cell line Coconnier et al 1992;Lehto and Salminen 1997;Tuomola and Salminen 1998), to colonize human volunteers based on faecal isolation after consumption of the bacteria (Goldin et al 1992;Saxelin et al 1991), and to be present on colonic biopsies (Alander et al 1997), indicating that in the case of Lactobacillus GG, the in vitro and in vivo results are in agreement. This contrasts with the results for the Lact.…”
Section: Discussionsupporting
confidence: 81%
“…Crociani et al (1995) reported bifidobacterial adhesion to Caco-2 cells to be inconsistent with human colonization by the same strains. Furthermore, probiotic Lactobacillus GG expressing high adhesion to ileostomy glycoproteins in the current study has been shown to adhere to the Caco-2 cell line Coconnier et al 1992;Lehto and Salminen 1997;Tuomola and Salminen 1998), to colonize human volunteers based on faecal isolation after consumption of the bacteria (Goldin et al 1992;Saxelin et al 1991), and to be present on colonic biopsies (Alander et al 1997), indicating that in the case of Lactobacillus GG, the in vitro and in vivo results are in agreement. This contrasts with the results for the Lact.…”
Section: Discussionsupporting
confidence: 81%
“…23 The ability of Lactobacillus GG to survive in the intestinal canal 12,24 and to colonize the gastrointestinal tract 13,25 has been shown for both adults and children. 26 In healthy intestines, the colonization is prolonged for about 1 week, 25 but the colon of one patient with ulcerative colitis was not colonized by Lactobacillus GG.…”
Section: Discussionmentioning
confidence: 99%
“…26 In healthy intestines, the colonization is prolonged for about 1 week, 25 but the colon of one patient with ulcerative colitis was not colonized by Lactobacillus GG. 13 Our knowledge of the ability of Lactobacillus GG to colonize the human small bowel after colectomy is limited. In our trial, Lactobacillus GG was recovered in the faecal flora in 40% of cases, but was not found in mucosal biopsies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for focusing on Lactobacillus rhamnosus strains is tied to many studies, in which the positive effects of the attachment of this particular micro-organism to human intestinal mucosa are reported [3,19,30,31,35,37].…”
Section: Introductionmentioning
confidence: 99%